Minimalisasi Risiko Operasional dan Risiko Keuangan pada UMKM Kerupuk Tengiri - Nur Ainiyah; Hari Setiono; Kasnowo; M. Bahril Ilmiddaviq (Lembaga Pengembangan Kinerja Dosen, 2024)
MSMEs that were once considered economically resilient during times of crisis were found to have a higher vulnerability to experiencing losses than large companies. This vulnerability is due to financial and non-financial constraints. Specifically, these obstacles are classified into operational risk, financial risk, and marketing risk. This activity aims to increase the knowledge and understanding of MSME players regarding HR and financial management to minimize operational and financial risks. This activity uses the methods of Counseling and Education as well as Mentoring and Coaching. The result is that this activity can be carried out successfully. Successful implementation is marked by the division of employee duties so that each employee has their responsibility for a job which can lead to increased employee performance. Apart from that, partners already understand the importance of financial management and its relevance for business development and decision-making. However, partners still do not know how to prepare financial reports by MSME).